Student Management in Improving Non-Academic Achievement - Zainuddin, Zaidah; Haslina, Haslina; Rahmawati, Rahmawati; Syahril, Syahril (DIDAKTIKA, 2023)
This study investigates the management of students in improving non-academic achievements at SMK Negeri 1 Bone, focusing on the planning, implementation, and evaluation processes involved in student management. Data were collected through interviews, observations, and documentation. A qualitative research method was employed for data analysis and conclusion drawing. The results show that the management of students to improve non-academic achievements at SMK Negeri 1 Bone has been effectively executed, as indicated by key actions such as the establishment of new student committees, recruitment, selection, orientation, grouping, reporting, evaluation, and student development. These management practices have led to the successful facilitation of extracurricular activities that help students realize their potential in various non-academic fields, including sports, arts, and leadership. The study concludes that enhancing the student management system can lead to the development of superior schools, with quality and capable graduates.